The Effect of Two-Mile Jogging Training on Lung Function Values in TNI Soldier Kodam I/Bukit Barisan - Rifda Hayati; Nuryunita Nainggolan; Amira Permatasari Tarigan; Putri Chairani Eyanoer (Indonesian Society of Respirology (ISR), 2020)
Background: Military soldiers are army personnel who are required to have good physical endurance and optimal fitness, include. So, it's needed physical exercise, include to be able to improve lung function. One parameter that can reflect physical fitness are lung function and m VO2max. This study aims to determine whether there is a relationship between physical exercise in the form of 2-mile jogging with increased lung function and VO2max of military soldiers Kodam 1 Bukit Barisan Methods: This research is an experimental study carried out in February-April 2019 against the TNI soldiers of the Bukit Barisan Military District 1. The research subjects were divided into two groups, group 1 who underwent regular 2-mile jogging exercises 3-5 times a week with a duration of 25 minutes for 2 months, and group 2 who underwent non-routine jogging exercises (less than 3 times a week). Lung function was assessed by spirometry. Results: As many as 68 military soldiers were involved in this study which were divided into two groups, 38 people in the group 1 who routinely trained and 30 people in group 2 that did not routinely practice. Group 1 VEP1 values were higher than group 2 (p=0.03). No significant differences in terms of KVP, MVV and VO2max in both groups. Lung function of smokers were lower than non-smokers, but not statistically significant. Conclusion: There were significant differences in VEP1 values between military soldiers who routinely and did not routinely undergo 2-mile jogging exercises.